2020
DOI: 10.1093/europace/euaa018
|View full text |Cite
|
Sign up to set email alerts
|

Termination of persistent atrial fibrillation by ablating sites that control large atrial areas

Abstract: Aims  Persistent atrial fibrillation (AF) has been explained by multiple mechanisms which, while they conflict, all agree that more disorganized AF is more difficult to treat than organized AF. We hypothesized that persistent AF consists of interacting organized areas which may enlarge, shrink or coalesce, and that patients whose AF areas enlarge by ablation are more likely to respond to therapy. Methods and results  We mappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…It represents fibrillatory conduction at one end, and pivoting, wavefront propagation through an isthmus (acceleration) as well as source‐sink mismatch in other aspects. Further studies on delineating anatomical areas of LIA would offer the opportunity to determine whether it is of mechanistic importance or a bystander phenomena of AF as shown in the latest results of panoramic AF recordings 21 …”
Section: Discussionmentioning
confidence: 99%
“…It represents fibrillatory conduction at one end, and pivoting, wavefront propagation through an isthmus (acceleration) as well as source‐sink mismatch in other aspects. Further studies on delineating anatomical areas of LIA would offer the opportunity to determine whether it is of mechanistic importance or a bystander phenomena of AF as shown in the latest results of panoramic AF recordings 21 …”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cases have more than one driver and are of types II and III. Previous studies have shown that AF is organized into interacting areas, 9,22 which may shrink, enlarge, or even merge during ablation and are similar to the driver regions in this paper.…”
Section: Discussionmentioning
confidence: 58%
“…From the activation fronts we determined a wavefront field (WFF) describing conduction propagation using stream lines. These streamlines can be used to determine rotational activity within the mapped domain using the vector curl of the flow velocity (Vidmar et al, 2016;Bhatia et al, 2020). Specifically, the rotational activity can be quantified by the vorticity Ω, which takes on values between -1 and +1, with negative/positive values corresponding to counterclockwise/ clockwise rotating spiral waves.…”
Section: Clinical Mapping and Ablationmentioning
confidence: 99%